Coronavirus pandemic: treatment and future prevention - Lundstrom, Kenneth (Future Microbiol, 2020)
The rapid spread of SARS-CoV-2 leading to the COVID-19 pandemic with more than 400,000 deaths worldwide and the global economy shut down has substantially accelerated the research and development of novel and efficient COVID-19 antiviral drugs and vaccines. In the short term, antiviral and other drugs have been subjected to repurposing against COVID-19 demonstrating some success, but some excessively hasty conclusions drawn from significantly suboptimal clinical evaluations have provided false hope. On the other hand, more than 300 potential therapies and at least 150 vaccine studies are in progress at various stages of preclinical or clinical research. The aim here is to provide a timely update of the development, which, due to the intense activities, moves forward with unprecedented speed.